Analysis of the relationship between climate change and land use change using the ESA CCI land cover maps in Sungai Kelantan Basin, Malaysia - Yi, Lin Tew; Mou, Leong Tan; Kwok, Pan Chun; Narimah Samat,; Mohd Amirul Mahamud, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Climate and land use land cover (LULC) are two major key drives that affect the hydrological cycle pattern within a river basin. This study aims to evaluate the capability of the European Space Agency Climate Change Initiative land cover (ESA CCI LC) product in representing land use pattern in Sungai Kelantan Basin (KRB), Malaysia; to analyze the changes of rainfall, maximum and minimum temperatures of the KRB from 1979 to 2018; and to assess the relationships between climate and land use changes within KRB. The results show that the ESA CCI LC product is applicable to represent LULC of the KRB, with an overall accuracy of 74.72% and a Kappa coefficient of 0.66. Trend analysis indicates that maximum and minimum temperatures of the KRB increased significantly at 95% confident level by 0.01 to 0.03 °C/year and 0.01 to 0.05 °C/year, respectively. Whereas annual precipitation at the Pos Hau, Pos Bihai, Pos Gob, and Kuala Krai stations increased significantly with the rates of 17.5 to 29.74 mm/year. The correlation shows that urban expansion in Gua Musang had a strong correlation with annual rainfall with a correlation coefficient (CC) value of -0.78. Furthermore, the conversion of forest into croplands over the Tanah Merah increased the minimum temperature significantly, with a CC value of -0.73. The findings show that the changes of land use in the middle basin contributed to the variations in temperature.